Realization of home physical therapy services in Poland and the United States – a comparative study - Mroczek, Bożena; Jaraczewska, Ewa; Wolińska, Weronika; Kurpas, Donata (Family Medicine & Primary Care Review, 2017)
Home physical therapy is considered the most important health experience ensuring independence for disabled or older people. This aim is achieved by providing steady long-term care focused on the individual needs of patient and helping them improve their health literacy. The aim of this article is to discuss the possibility of using standardized questionnaires to measure changes in health status and the functional abilities of patient based on experiences in other countries. The article describes the home physical therapy system in Poland and the United States, based on current laws and scientific research. The following terms were included: outpatient physical therapy, home physical therapy, health literacy, tests to evaluate functionality of patient. The Barthel scale, used in Poland, does not take into account all elements of functional evaluation, and thus it does not allow authors to measure and evaluate changes in the functional abilities of the patient. One example of such a questionnaire is the Outcome and Assessment Information Set-C1 (OASIS -C1), used in the US . Realization of home physical therapy for patients requiring help may be an important factor in changing the range of their independence, thus having an influence on improving their quality of life. The use of a validated OASIS questionnaire and the Barthel scale to perform a functional evaluation of patients will lead to providing services more suitable to the health status of patients and a systematic evaluation of changes in the functional abilities of patients. Improving the health competence of patients will have an impact on the conscious use of health services financed through public and private funds.